STRATEGI DIVERSIFIKASI TERHADAP PERFORMA PERUSAHAAN DENGAN EFEKTIVITAS KOMITE AUDIT SEBAGAI VARIABEL PEMODERASI - Andyan Adhimukti; Rinaningsih Rinaningsih; Retno Yuliati (Jurnal Akuntansi, 2018)
This study aims to investigate the influence of industrial and geographical diversification strategy on company performance. In addition, this study also aims to analyze how audit committees using proxies by ASEAN CG Scorecard will be moderating the relationship between diversification strategies on company performance. The study uses sample of 64 Indonesian manufacturing companies in 2011 to 2016 with a total observation of 378 firm-years. The result shows that both industrial and geographical diversification strategy is not significant to company performance. After the effectiveness of the audit committee moderating on industrial diversification strategies, this study shows that an effective audit committee has no effect on performance But when the the effectiveness of the audit committee moderating on geographic diversification variables, the results of the research show significant negative impact.Keywords : industrial diversification, geographic diversification, audit committee, performance, ASEAN CG Scorecard